Depressão, ansiedade, insônia e burnout em estudantes de Medicina durante a pandemia da covid-19 - MELO, Débora Leão (2022)
Quarantine and social isolation are strategies that are being used to contain the spread of COVID-19, an infection caused by sars-cov-2, known as the new coronavirus. But in addition to the danger of physical illness from the new virus, there is still a greater risk of mental illness due to the pandemic scenario. In addition, several studies show that medical students are more likely to develop problems related to mental health than the general population. Objective: To assess the perception and psychological effects of social isolation in the COVID-19 pandemic situation. Method: The target audience was students from the medical school of the Federal University of Pará — Campus Altamira. It was a cross-sectional quantitative study carried out from a survey of information through Survey, through the Google Forms platform. Descriptive and inferential statistical analyzes were performed according to the data obtained. Results: 194 responses were obtained from the 223 students enrolled in the course. Of the sample, 64 (32.98%) had a positive score for generalized anxiety disorder, 100 (51.54%) for insomnia symptoms, 73 (37.62%) for major depression and 8.24% for burnout during the pandemic period. It is concluded that medical students seem to be more susceptible to mental illness and the COVID 19 pandemic can intensify the suffering. Thus, more studies are needed to clarify the causal determinants, as well as more active interventions aimed at the mental health of medical students.